Inversion Pattern and Functional Shifts of The Verb ‘Ada’ in Indonesian Sentences - Encep Kusumah; Nunung Sitaresmi; Rudi Adi Nugroho M.Pd.; Meilani Puji Astini (Tabasa: Jurnal Bahasa, Sastra Indonesia, dan Pengajarannya, 2026)
This study was motivated by the frequent use of sentences with the verb ada that require structural analysis, with the focus of the study directed toward the syntactic function of these sentences The data, consisting of 194 sentences composed by students in an academic context, were selected purposively and analyzed using a descriptive method based on Verhaar’s theory. The results reveal four constructions: N+Va, Va+N, N+Va+Num, and N+Va+N, with the Va+N construction being the most prevalent; verbs ada are always function as predicates and follow an inverted word order (P–S). These sentences are classified as simple and complex sentences with a variety of structural patterns. Furthermore, a shift in the category of the verb ada to an adverb was observed when it co-occurs with numerals, indicating its adaptability as an active element within numeral phrases, rather than merely a passive component, particularly in graded complex clause. This study demonstrates that the syntactic behavior of verbs ada constitutes a movement of verbs in occupying linguistic units at the syntactic level, namely the movement of verbs within grammatical units such as phrases, clauses, and sentences. The implications of these findings include up-to-date guidelines for teaching scientific sentence structure, analyzing academic discourse, and serving as a lexicographical reference to enrich grammatical information on word classes in monolingual Indonesian dictionaries.   Penelitian ini dilatarbelakangi oleh banyaknya penggunaan kalimat beverba ada yang memerlukan analisis struktural, dengan fokus kajian diarahkan pada fungsi sintaksis kalimat tersebut. Data berupa 194 kalimat yang disusun mahasiswa dalam konteks akademik dipilih secara purposif dan dianalisis menggunakan metode deskriptif dengan teori Verhaar. Hasil menunjukkan empat konstruksi: N+Va, Va+N, N+Va+Num, dan N+Va+N, yang didominasi konstruksi Va+N; verba ada selalu berfungsi sebagai predikat dan berpola inversi (P–S). Kalimat-kalimat tersebut terklasifikasi dalam kalimat tunggal dan majemuk bertingkat dengan variasi pola yang beragam. Selain itu, ditemukan pergeseran kategori verba ada menjadi adverbia ketika berdampingan dengan numeralia menunjukkan adaptabilitasnya sebagai unsur aktif dalam frasa numeral, bukan sekadar komponen pasif, terutama dalam klausa kompleks bertingkat. Penelitian ini menujukkan perilaku sintaktis verba ada merupakan gerak verba dalam menempati satuan bahasa pada tataran sintaksis, yakni pergerakan verba pada satuan gramatika frasa, klausa, maupun kalimat. Implikasi temuan ini meliputi panduan mutakhir dalam pengajaran struktur kalimat ilmiah, analisis wacana akademik, serta rujukan leksikografi untuk memperkaya informasi gramatikal kelas kata dalam kamus ekabahasa bahasa Indonesia.